Leukapheresis in acute myeloid leukemia patients with hyperleukocytosis: A single center experience. Issue 2 (October 2015) - Berber, Ilhami; Kuku, Irfan; Erkurt, Mehmet Ali; Kaya, Emin; Gozukara Bag, Harika; Nizam, Ilknur; Koroglu, Mustafa; Ozgul, Mustafa; Bazna, Sezai
Abstract: Hyperleukocytosis is defined as WBC count above 100, 000/mm 3 in peripheral blood. Increased WBC count leads to leukocyte aggregation, increased blood viscosity, and consequently results in stasis in small blood vessels. Ultimate neurological, pulmonary, gastrointestinal complications, coagulopathy, and tumor lysis syndrome cause increase in morbidity and mortality. Leukapheresis is a treatment modality used for hyperleukocytosis. In patients presenting with hyperleukocytosis the indications for leukapheresis were accepted as having symptoms of leukostasis and prophylactic. Indications for leukapheresis in prophylactic group evaluated according to WBC count. We report a single center experience about leukapheresis in managing 31 AML patients with hyperleukocytosis. In addition to demographic characteristics, disease-related clinical and laboratory findings of the patients were recorded. Survival rates were also calculated. Ten patients were female. The most common of AML subtype was AML-M2. The median number of leukapheresis per patient was 2 and totally 60 leukapheresis cycles were performed in all patients. There was a significant decrease in WBC count and LDH level after leukapheresis as compared with the baseline values (p < 0.05). Early and total mortality were 16.1% and 58.0%, respectively. Alive and died patients were evaluated according to baseline WBC, LDH; increased WBC count and LDH level were found in died patients (p < 0.05). According to leukapheresis indications, patients were divided into two groups: 14 patients in symptomatic leukostasis, 17 patients in prophylaxis. No statistically significant differences were noted between both groups in leukapheresis effectiveness, mean survival time, early and total mortality rate (p > 0.05). None of our patients suffered serious side effects and tumor lysis syndrome during or after apheresis. Leukapheresis is an effective and safe approach to reduce WBC counts in patients with AML with hyperleukocytosis. Further evidence-based data obtained from larger sample sizes are required to better understand the impact of prophylaxis leukapheresis on early and total mortality of AML patients with hyperleukocytosis.